Metabolic activity of peripheral blood neutrophils in patients with Opisthorchis felineus invasion and skin syndrome - V. V. Tsukanov (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
The aim was to examine functional activity of peripheral blood neutrophilic granulocytes in patients with Opisthorchis felineus invasion and skin syndrome. Materials and methods. A total of 92 patients with chronic opisthorchiasis were examined, of which 38 patients (20 males and 18 females, average age 35.7±3.9 years) and 54 patients (28 males and 26 females, average age 36.5±4.1 years) with/without skin syndrome, as well as 32 apparently healthy subjects (17 males and 15 females, average age 41.5 years). Detection of adult parasite eggs or bodies in the duodenal contents and/or feces was used as the major diagnostic method of opisthorchiasis used in all 92 opisthorchiasis patients. Liver fibrosis was assessed by elastometry method according to the METAVIR scale in all 92 opisthorchiasis patients. Functional activity of peripheral blood neutrophilic granulocytes was examined in all 92 opisthorchiasis patients and 32 healthy individuals from the control group by chemiluminescent analysis measuring intensity of reactive oxygen species production in spontaneous and zymosan-induced reactions in lucigenin and luminol-dependent processes. Results. Opisthorchiasis patients with vs. without skin syndrome suffered at higher rate from pain in the right hypochondrium, dyspepsia, astheno-vegetative syndrome, skin itching, blood eosinophilia, hyperbilirubinemia, cholestatic syndrome, cholecystitis, hepatomegaly, and had elevated serum immunoglobulin E level. Liver fibrosis F3—F4 according to METAVIR was determined in 18.4% and 11.1% of opisthorchiasis patients with vs. without skin syndrome (OR = 1.78; CI 0.57—5.57; p = 0.05). Both luminol- and lucigenin-dependent processes in opisthorchiasis patients with vs. without skin syndrome revealed significantly decreased functional activity of neutrophilic granulocytes which was evidenced by significantly decreased maximum intensity of reactive oxygen species production and the area under the chemiluminescence curve both in spontaneous and zymosan-induced reaction. Conclusion. The results suggest that the presence of skin syndrome in patients with opisthorchiasis is accompanied by more prominent clinical and laboratory manifestations, decreased functional activity of peripheral blood neutrophils, thereby allowing to consider it as a marker of intense pathology.